Assessorias e coberturas jornalísticas na administração pública municipal - Machado, Bruno Soares (2015)
The purpose of this dissertation is to analyze the interaction between press offices of Brazilian municipalities and local newspapers. To this end, two municipalities are analyzed, observing the relationship between the public relations arm of mayoral offices and salient press vehicles. The study evaluates how often newspapers publish government releases on their pages - which may suggest the extent of press independence. Case studies examine the cities of Bauru and Piracicaba, - which, besides being prosperous cities, located in the state of São Paulo, have several characteristics in common, such as the number of inhabitants, the municipal budget, economic output and human development Index scores. The study thus uses a similar systems, controlled comparison to understand variation in local media independence in one of Brazil`s wealthier regions. The analysis broaches the theory of agenda setting, and the relationship between media and democracy. Research shows that there is a high degree of correspondence between governmental press releases and local newspaper coverage in the city of Bauru. Whereas the Jornal da Cidade aired matters related to City Hall, including identical to full or partial releases, 48% of the time, in the case of the Jornal de Piracicaba, only 5% of the news items contained text partially or completely related to releases published by the mayor`s office. The evidence thus indicates a high degree of governmental media capture in Bauru and high independence in Piracicaba. An analysis of both cities illustrates that the most likely explanation has to do with media competition or the lack thereof.